O eu como produto do tempo e da memória: uma leitura de angústia, de Graciliano Ramos - Vásquez, Marta Maria de Lima (2007)
The objective of our research is to perceive in the romance Angustia, of Graciliano Ramos, how the universe space-temporality of the told events, in the plan of the discursive articulation of the main personage simulacrum of the literal proposal functions textual, and as the presence of the subject is not restricted only to the marks of the person or the use of the certain verbal times. Our proposal is developed in three stages. The first one of it consists of general gathered what it is time in the texts of Saint Augustine and Marcel Proust. We raise some relative aspects to the insertion of the man in the time and to the concept of involuntary memory. Over all, in what it respects to this last secular modality, the research of Jeanne Marie Gagnebin had been determinative for the reading that we made. In the second part, we not only analyze the romance to the light of the concept of present time in the two cited authors, we also adopt the modern conception of time of Anatol Rosenfeld, the time of the nightmare , as an activity of inherent complexity when making human being. In the third chapter, it was tried to give relief, by means of the unfolding of the voice, to the recovery of the memory and the imagination under the writing form: the bookwill. In this direction, the considerations of Maurice Blanchot, developed in O livro por vir (The Book for coming), had served to base the relative readings and considerations to the memory and the reminiscences